(untitled) (Global Journals of Research in Engineering, 2011)
Aluminium is a very reactive metal with a high affinity for oxygen. Nevertheless, the metal behaves as resistant to corrosion under most environmental conditions due to inert and protective character of the aluminium oxide film which forms naturally on the metal surface. Thus in most environments, the rate of corrosion of aluminium decreases rapidly with time. These properties exhibited by aluminium are also present in the alloys of aluminium; though the protection given will depend upon the type of alloy and its condition.#xD; 1.2 There are however a number of conditions, commonly encounte red, under which aluminium#xD; gets extensively corroded. The corrosion takes place either through the pores in the oxide film or#xD; in the areas from which the oxide film has been removed due to abrasion under normal environmental conditions. Also under certain circumstances, the protective film does not form at all leading to high rate of corrosion.